2012
DOI: 10.4103/0975-3583.95379
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal syndrome: Resistant to diuretics, sensitive to ultraflitration

Abstract: Cardiac and renal diseases are becoming increasingly common today, and are seen to frequently coexist, thus causing a significant increase in the mortality rate, morbidity, complexity of treatment and cost of care. Syndromes describing the interaction between heart and kidney have been defined and classified; however, never as a result of a consensus process. Though the incidence of cardiorenal syndrome is increasing, the associated pathophysiology and effective management are still not well understood. For ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…RAS activation has also been implicated in the development of cardiac fibrosis in CKD and ESRD patients 74 78 . Evidence from multiple randomized clinical trials supports the notion that inhibiting the RAS improves all causes of mortality and reduces adverse cardiovascular events and strokes, which is not commonly seen with other antihypertensive medications 64 , 79 81 . RAS inhibition has been widely utilized in managing patients with CVD, especially with co-morbidities of CKD or diabetes mellitus 82 87 .…”
Section: Discussionmentioning
confidence: 89%
“…RAS activation has also been implicated in the development of cardiac fibrosis in CKD and ESRD patients 74 78 . Evidence from multiple randomized clinical trials supports the notion that inhibiting the RAS improves all causes of mortality and reduces adverse cardiovascular events and strokes, which is not commonly seen with other antihypertensive medications 64 , 79 81 . RAS inhibition has been widely utilized in managing patients with CVD, especially with co-morbidities of CKD or diabetes mellitus 82 87 .…”
Section: Discussionmentioning
confidence: 89%
“…A recently published study conducted on surgical patients undergoing congenital heart disease surgery on cardiac bypass; revealed 28% of patients developing AKI, both children and adult population were included in this study (7). When search made for other regional studies; a case report found from India reporting diuretic resistance and later developing CRS was found (8). Another original Naqvi article from India highlighting predictors of CRS type 1 in patients with acute right ventricular dysfunction indicated diabetes and presentation in state of shock as poor prognostic markers in their series (9).…”
Section: Discussionmentioning
confidence: 98%